Effect of carbon nanotube on morphology and mechanical properties of nickel/graphene oxide coating on copper substrate - Aghaee Malayeri, Mahdi; Tajally, Mohammad; Koohestani, Hassan (Journal of Composites and Compounds, 2025)
A novel nickel-graphene oxide/carbon nanotube (Ni/GO/CNT) composite coating was deposited on a copper substrate via the electrodeposition method with different Concentration of CNT (0.5, 1 and 1.5 g/L). In this paper, the effect of CNT addition on the mechanical properties and morphology was investigated. For phase analysis, X-ray diffraction was performed, but the peak related to GO was not identified. Raman results confirm the presence of GO and CNT in Ni/GO/CNT coatings. The composite coatings with 1 g/L of CNT exhibited the maximum hardness, with a value of 840 HV. Furthermore, Ni/G0.5O/1CNT coating showed excellent adhesion strength, and minimum wear loss (0.0002 g). However, further addition CNT to 15 g/L led to a decrease in hardness. This is attributed to the agglomeration of CNT, which weakens the integrity of the structure.